La enseñanza de la religión en el sistema educativo costarricense: dificultades actuales y posibles soluciones en el marco de una sociedad plural - Antonio Pizarro-B (Revista Electronic@ Educare, 2007)
This article seeks to be a contribution to the debate on the theaching of the religion in the Costa Rican educational system. This debate has become public starting from the publication May 1º 2005 of a Pronouncement of the University Council (CU) of UNA (National University).First the teaching of the religion is located in the concrete context of the country, he offers a pertinent definition of religion and its implications like premises to understand the polemic, the reactions are analyzed that the Official statement has generated and finally coinciding and supporting the CU and the EECR (Ecumenical school of sciences of the religion) intends some measures that could contribute to find inclusive, democratic solutions, chords with the effective confesional pluralism of the Costa Rican society.